Supporting Historical Structures Technical Condition Assessment by Monitoring of Selected Physical Quantities. (2017) - Bednarski, Łukasz; Sieńko, Rafał; Howiacki, Tomasz
Abstract: Assessment of historical structures technical condition is difficult due to the lack of technical documentation and inability to clearly identify the strength-strain characteristics of materials, from which they were erected. Thus, creating numerical models of objects made many years ago, is very complicated and the results reliability is very limited. The article describes an example of structural health monitoring system application, which aim was to perform continuous, remote and automatic measurements of selected physical quantities, important for crack state estimation in the walls and other structural members in historic, parish St. John the Baptist Church in Jangrot (Poland). When designing the system, the attention was paid to minimize costs by selecting optimum number of measuring points and an appropriate measuring technology, as well as a small interference in historical substance. Measurement data collected during 12 months were the basis for assessment of structure technical condition.